Erythroxylaceae, erythroxylum subsessile (Mart.) O.E. schulz in Espírito Santo: Distribution extension - Barbosa, Suzana Bissacot [UNESP] (My University, 2012)
Erythroxylaceae have tropical and subtropical distribution with four genera and about 250 species. Erythroxylum is the biggest genus of the family with approximately 100 species cited for Brazil. Erythroxylum subsessile (Mart.) O.E. Schulz is a species cited just for Rio de Janeiro state and now first recorded for the state of Espírito Santo, increasing its area of distribution. © 2012 Check List and Authors.
Keywords: Erythroxylaceae; Erythroxylum